Pharmacokinetics and Metabolism of Cyadox and Its Main Metabolites in Beagle Dogs Following Oral, Intramuscular, and Intravenous Administration - Sattar, Adeel; Xie, Shuyu; Huang, Lingli; Iqbal, Zahid; Qu, Wei; Shabbir, Muhammad A.; Pan, Yuanhu; Hussain, Hafiz I.; Chen, Dongmei; Tao, Yanfei; Liu, Zhenli; Iqbal, Mujahid; et al. (Frontiers in Pharmacology, 2016)
Cyadox (Cyx) is an antibacterial drug of the quinoxaline group that exerts markedly lower toxicity in animals, compared to its congeners. Here, the pharmacokinetics and metabolism of Cyx after oral (PO), intramuscular (IM) and intravenous (IV) routes of administration were studied to establish safety criteria for the clinical use of Cyx in animals. Six beagle dogs (3 males, 3 females) were administered Cyx through PO (40 mg kg-1 b.w.), IM (10 mg kg-1 b.w.) and IV (10 mg kg-1 b.w.) routes with a washout period of 2 weeks in a crossover design. Highly sensitive high-performance liquid chromatography with ultraviolet detection (HPLC-UV) was employed for determination of Cyx and its main metabolites, 1, 4-bisdesoxycyadox (Cy1), cyadox-1-monoxide (Cy2), N-(quinoxaline-2-methyl)-cyanide acetyl hydrazine (Cy4) and quinoxaline-2-carboxylic acid (Cy6) in plasma, urine and feces of dogs. The oral bioavailability of Cyx was 4.75%, suggesting first-pass effect in dogs. The concentration vs. time profile in plasma after PO administration indicates that Cyx is rapidly dissociated into its metabolites and eliminated from plasma earlier, compared to its metabolites. The areas under the curve (AUC) of Cyx after PO, IM and IV administration were 1.22 h×µg mL-1, 6.3 h×µg mL-1, and 6.66 h×µg mL-1, while mean resident times (MRT) were 7.32, 3.58 and 0.556 h, respectively. Total recovery of Cyx and its metabolites was >60% with each administration route. In feces, 48.83% drug was recovered after PO administration, while 18.15% and 17.11% after IM and IV injections, respectively, suggesting renal clearance as the major route of excretion with IM and IV administration and feces as the major route with PO delivery. Our comprehensive evaluation of Cyx has uncovered detailed information that should facilitate its judicious use in animals by improving understanding of its pharmacology.